Merancang Sistem Pengukuran Redaman Transmisi Kabel Optik Single Mode Jenis Pigtail - aprinal adila asril; Yustini yustini; Putri Azizah Herwita (Teknik Elektro Politeknik Negeri Padang, 2019)
Optical fiber is a transmission channel made of glass or plastic that is used to transmit light signals from one place to another. Optical fibers, in general, have a basic structure consisting of a fiber core, a fiber coating (cladding), and a protective layer (coating) consisting of an inner jacket. This research discusses the design of the attenuation of the fiber optic transmission measurement system by connection factor. Optical fiber cable used in this research is pigtail type cable with single-mode cable type. The cable used is 10 meters long, which will be installed in the Optical Termination Box. In the Optical Termination Box there are 6 pigtail cables, which are without connections, with a 6 cm sleeve protection one connection and two connections, also with a 4 cm sleeve protection one connection and two connections, then use a barrel adapter. In this design testing tools use Light source, Optical Power Meter, and Optical Time Domain Reflectometer). The attenuation value after testing on the protection sleeve 6cm; 12,330 dB, then the attenuation on the protection sleeve is 4cm; 12,729 dB. Then attenuation on the barrel adapter; 12,954 dB